Chile : Staff Report for the 2000 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2000)
Chile's overall economic performance during 1990-97 was very strong. By early 1998, Chile faced the difficult combination of a widening external current account deficit and a slowdown of capital inflows. The authorities scaled back expenditure plans and tightened monetary policy strongly to prevent a large depreciation of the currency. Executive Directors welcomed the new three-pillar framework for policies consisting of conservative, rules-based fiscal and monetary policies, greater emphasis on sound supervisory and regulatory frameworks, as well as new social policies.